A gendered field in a transnational setting: portuguese hindu-gujaratis - Lourenço, Inês; Cachado, R. (Transdiciplinary Ethnography in India, 2021)
This chapter is about the ethnographic relationship with Portuguese hindu-gujaratis during fieldwork conducted in Portugal, United Kingdom, India and Mozambique. In the introduction we give an overview about the previous studies on this population that provides general information about their transnational trajectories, social, economic and political contexts. We then turn directly to build on gender challenges in the field, from the discussion about being women and working mostly with women interlocutors, to learning how to behave in different settings, in daily live, what to wear, among other. Then, we explore our access to religious practices, through the description of how we had access to the temples and what it implies being a woman. We give examples with fieldnotes that illustrate our baby steps on our ethnographic field to pass the test. By the end of the day, we were treated as daughters with its advantages and potential pitfalls. The next part reflect about the adaptation to new gender patterns in an ethnographic field where we related more with women, and how our identities and how we were differently identified by our interlocutors, led us to deepen our debates on ethics in the fieldwork, which is, ultimately, what we aim to do with this chapter. The section entitled the gender of mutuality opens the discussion about ways of retribution in the field and how the mutuality process contributes to overcome classical oppositions, such as the private and the public sphere, both in the field and outside, in the civil society.